2023
DOI: 10.1038/s41598-023-42601-4
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein-to-albumin ratio as a biomarker in patients with sepsis: a novel LASSO-COX based prognostic nomogram

Xin Zhou,
Shouzhi Fu,
Yisi Wu
et al.

Abstract: To develop a C-reactive protein-to-albumin ratio (CAR)-based nomogram for predicting the risk of in-hospital death in sepsis patients. Sepsis patients were selected from the MIMIC-IV database. Independent predictors were determined by multiple Cox analysis and then integrated to predict survival. The performance of the model was evaluated using the concordance index (C-index), receiver operating characteristic curve (ROC) analysis, and calibration curve. The risk stratifications analysis and subgroup analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…On the other hand, immune imbalance can also result in anti-inflammatory hyperactivity and the production of anti-inflammatory cytokines, which affected immune cell functions and disrupted the body’s equilibrium. Inflammation markers were crucial indicators throughout the development of sepsis ( 39 ). CRP, a commonly used inflammatory marker in clinical practice, had been studied for its prognostic efficacy in sepsis ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, immune imbalance can also result in anti-inflammatory hyperactivity and the production of anti-inflammatory cytokines, which affected immune cell functions and disrupted the body’s equilibrium. Inflammation markers were crucial indicators throughout the development of sepsis ( 39 ). CRP, a commonly used inflammatory marker in clinical practice, had been studied for its prognostic efficacy in sepsis ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation markers were crucial indicators throughout the development of sepsis ( 39 ). CRP, a commonly used inflammatory marker in clinical practice, had been studied for its prognostic efficacy in sepsis ( 39 ). Studies had shown that elevated CRP levels in sepsis patients were associated with increased risk of in-hospital mortality rates and short-term mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In sepsis patients, high CRP and low albumin levels are linked with outcomes. [37] Furthermore, compared with OHCA patients, IHCA patients had higher CRP and lower albumin levels, which correlated with patient outcomes. [8,32] Therefore, the distinctive high CRP and low albumin levels in IHCA patients, as opposed to those in OHCA patients, may be indicative of prognosis, aligning with the findings of the present study.…”
mentioning
confidence: 94%
“…K-M curves showed higher in-hospital mortality in high CAR patients. Sepsis survival is accurately predicted by CARbased model 14. Chen J et al examined 196 advanced NSCLC patients treated with anlotinib from June 2018 to June 2021 in 2023.…”
mentioning
confidence: 99%